Biophysical characterization and single‐chain Fv construction of a neutralizing antibody to measles virus. (22nd July 2019) - Tadokoro, Takashi; Jahan, Mst Lubna; Ito, Yuri; Tahara, Maino; Chen, Surui; Imai, Atsutoshi; Sugimura, Natsumi; Yoshida, Koki; Saito, Mizuki; Ose, Toyoyuki; Hashiguchi, Takao; Takeda, Makoto; et al.
Abstract : The measles virus (MV) is a major cause of childhood morbidity and mortality worldwide. We previously established a mouse monoclonal antibody, 2F4, which shows high neutralizing titers against eight different genotypes of MV. However, the molecular basis for the neutralizing activity of the 2F4 antibody remains incompletely understood. Here, we have evaluated the binding characteristics of a Fab fragment of the 2F4 antibody. Using the MV infectious assay, we demonstrated that 2F4 Fab inhibits viral entry via either of two cellular receptors, SLAM and Nectin4. Surface plasmon resonance (SPR) analysis of recombinant proteins indicated that 2F4 Fab interacts with MV hemagglutinin (MV‐H) with a K D value at the nm level. Furthermore, we designed a single‐chain Fv fragment of 2F4 antibody as another potential biopharmaceutical to target measles. The stable 2F4 scFv was successfully prepared by the refolding method and shown to interact with MV‐H at the μm level. Like 2F4 Fab, scFv inhibited receptor binding and viral entry. This indicates that 2F4 mAb uses the receptor‐binding site and/or a neighboring region as an epitope with high affinity. These results provide insight into the neutralizing activity and potential therapeutic use of antibody fragments for MV infection. Abstract : Measles is a major cause of childhood morbidity and mortality. Among the neutralizing antibodies reported, the mouse monoclonal antibody, 2F4, which targets measles virus hemagglutinin protein, has the potential to be used therapeutically against measles infection. We have constructed and characterized the antigen‐binding fragment (Fab) and single‐chain variable fragment of 2F4. The fragmented antibodies maintained the ability to inhibit receptor‐mediated membrane fusion in measles infection. These results highlight the therapeutic potential of antibody fragments for measles infection.